‘The scream of the mutes:’ gender politics and tactical innovation in Brazilian rural movements - Peschanski, João Alexandre (Teoria & Pesquisa Revista de Ciência Política, 2022)
Women have had in the 2000s a leading role in rural social movements in Brazil, including the Peasant Woman Movement (MMC), the Landless Workers’ Movement (MST) and in general the Brazilian section of Via Campesina. In the 1990s and early 2000s within the MST, women had remained marginal in the setting of national strategies, but the situation changed in face of a divide between male leaders, calling for a ‘truce’ with the government, and female leaders, striving for radicalization after the election of Luiz Inácio Lula da Silva, in 2002. Such divides explain to some extent the emergence of the MMC, a new actor in the rural struggles in Brazil, and eventually, tactical innovations and frame shifts of the MST itself.